The American species of the genus Glaucolepis Braun, 1917 (Neotrifurcula van Nieukerken, syn. nov.) (Lepidoptera: Nepticulidae) - Stonis, Jonas R.; Remeikis, Andrius; Diškus, Arūnas; Solis, M. Alma (Zootaxa, 2017)
We provide diagnostic characters for the genus Glaucolepis Braun, re-examine the type series of the type species of the North American G. saccharella Braun, describe two new species from Chile and Argentina (G. flagellata Remeikis & Stonis, sp. nov. and G. pseudoflagellata Remeikis & Stonis, sp. nov.), and provide the first photographic documentation of the central Andean G. aerifica (Meyrick). We synonymize Neotrifurcula van Nieukerken, 2016, syn. nov. with Glaucolepis and provide one new combination for the south Andean G. gielisorum (van Nieukerken, 2016), comb. nov. All species treated in the paper are illustrated with drawings and (or) photographs of the adults and genitalia.